Biofilter-constructed wetland-trophic pond system: A new strategy for effective sewage treatment and agricultural irrigation in rural area. (15th April 2023) - Peng, Xinxin; Yang, Wei; Jin, Qiu; Su, Shihua; Guo, Pan; Li, Ming; Liu, Huazu; Li, Wei
Abstract : Artificial ecosystems with high biological complexity are generally considered to be efficient in metabolizing substances and resistant to temperature shock. In this study, a novel near-natural system (BCT system), which consisted of simple biofilter, constructed wetland and trophic biology pond, was conducted to treat rural sewage in situ for irrigation into farmland. Water quality related to carbon and nutrients and microbial community were analyzed along the system to reveal the effect of each unit. The annual average removals of BCT system for TN, N H 4 + -N, TP and COD could reach 46.53%, 52.18%, 41.48%, and 53.21%, respectively. There was no significant decrease for removal efficiencies from high temperature period (HTP, ≥15 °C) to low temperature period (LTP, <15 °C). In LTP, the trophic pond (TRP) removed 34.85% of TN, 33.93% of N H 4 + -N, 13.71% of TP and 18.77% of COD, while the removal efficiencies of constructed wetland fluctuated greatly. The TRP facilitated the BCT system to maintain the removal capability during low temperature period. The relative abundance of denitrification functional genes in TRP increased nearly tenfold from HTP to LTP. The effluent quality from the system can meet the agricultural irrigation standards, demonstrating the effect of BCT system on sewage treatment and agricultural irrigation in rural area. Highlights: Near-natural BCT system is a robust treatment for rural wastewater. Trophic pond maintains the removal capability during low temperature period. Denitrification genes in trophic pond increased tenfold at low temperature. Effluent quality from BCT system meet the agricultural irrigation standards.